ANALISIS TINGKAT CAKAP DIGITAL SISWA DALAM ETIKA BERMEDIA SOSIAL PADA ERA SOCIETY 5.0 DENGAN MODEL RASCH - Wathroh Mursyidi; Nur Habibah (Journal of Education and Teacher Training Innovation, 2026)
The development of the Society 5.0 era demands that the younger generation not only master digital technology but also be able to apply ethics in the use of social media. The phenomenon of increasing student digital activity often has negative impacts, such as the spread of hoaxes, cyberbullying, and privacy violations. In this context, Islamic Religious Education is seen as important to shape students' digital character so that they are able to behave wisely and responsibly in accordance with Islamic teachings. This study aims to analyze the application of digitalization in Islamic Religious Education learning at SMPIT Insan Rabbani Bekasi, and to collect information of student level digital skills on social media ethics in the Society 5.0 era. The study used a quantitative method, and the data obtained are analyzed by the Rasch model with the Winsteps application. The study population was all students in grades VII, VIII, and IX at SMPIT Insan Rabbani Bekasi with a sampel used 109 respondents. The result of study indicate that the level of students digital skills is in the good category, as indicated by the average value of the person measure of 2.05 logit—higher than the item measure. This condition indicates that most students have adequate digital skills in terms of maintaining privacy, communicating politely, and avoiding the spread of invalid information.